2015
DOI: 10.3324/haematol.2014.112714
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptome and chromatin occupancy analysis reveal the short isoform of GATA1 is deficient for erythroid specification and gene expression

Abstract: GATA1 is a master transcriptional regulator of the differentiation of several related myeloid blood cell types, including erythrocytes and megakaryocytes. Germ-line mutations that cause loss of full length GATA1, but allow for expression of the short isoform (GATA1s), are associated with defective erythropoiesis in a subset of patients with Diamond Blackfan Anemia. Despite extensive studies of GATA1s in megakaryopoiesis, the mechanism by which GATA1s fails to support normal erythropoiesis is not understood. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 50 publications
3
41
0
Order By: Relevance
“…We have previously proposed that Gata2 is required for EKLF's initial activation, which is then activated to higher levels once Gata1 is fully induced by Gata2 (15). An intact Gata1 protein is required for full activation of EKLF, as Gata1s is deficient (95). The requirement of the BMP4 pathway for Gata1 expression suggests a coherent type 1 feed-forward mechanism on EKLF induction between BMP4/Smad5 and Gata1 once Gata1 is induced by Gata2 (96,97).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously proposed that Gata2 is required for EKLF's initial activation, which is then activated to higher levels once Gata1 is fully induced by Gata2 (15). An intact Gata1 protein is required for full activation of EKLF, as Gata1s is deficient (95). The requirement of the BMP4 pathway for Gata1 expression suggests a coherent type 1 feed-forward mechanism on EKLF induction between BMP4/Smad5 and Gata1 once Gata1 is induced by Gata2 (96,97).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations that lead to the expression of the GATA1s isoform are also observed in some patients with Diamond‐Blackfan anemia—a bone marrow failure syndrome characterized by macrocytic anemia . Genome‐wide studies have shown that GATA1s binding is impaired at erythroid target genes but not at megakaryocytic target genes …”
Section: Gata1mentioning
confidence: 99%
“…Comparison of chromatin binding signatures of GATA1 and GATA1s revealed that while GATA1s bound megakaryocytic genes normally, it bound many of its erythroid targets less efficiently than full-length GATA1 [21,22]. …”
Section: Human Gata1: One Gene But Two Isoforms Partially Different Fmentioning
confidence: 99%
“…This class of mutations results in exclusive production of a NH-terminally deleted isoform of GATA1 known as GATA1s [20]. With respect to the DBA phenotype, studies have shown that Gata1s fails to occupy chromatin of erythroid target genes to the same extent as the full-length protein, likely explaining the erythroid defect [21,22]. By contrast, the mechanism by which GATA1s causing mutations contribute to DS-AMKL is unknown.…”
Section: Introductionmentioning
confidence: 99%